Voz e representação do real: montagem e construção da narrativa no documentário brasileiro contemporâneo - Rocha, Patrício Alves Miranda da (2012)
This study aims to understand the production of Brazilian documentaries of today from one of its technical processes: the montage. We want this work to study the relationship between this stage of production and the construction of the narrative, since it is the montage process that the raw material takes shape, it is composed of images recorded for the film or image file, giving rise to the audiovisual work finalized. Undergirded by the main theories of montage and documentary filmmaking, we analyze how is the construction of their own voice in each of the films that comprise the corpus of this thesis. In the first case, we observed the relationship between the montage and construction of their own voice of the film based on the spoken word in the form of interviews and voice-over narration from the example of O fim e o princípio (2005), by Eduardo Coutinho. We take the device used in this film to apply the concepts of mounting evidence and modes of representation of Nichols (2009). In the second case we turn to the expressive use of montage features in the construction of a narrative content more poetic, this time analyzing the film Nós que aqui estamos por vós esperamos (1998), by Marcelo Masagão, where we observe the role of montage in process of "reframing" of archive images that make up the whole movie (BERNARDET, 1999). Thus, starting from two distinct forms of montage, we sought to understand the most comprehensive way possible to mount as the place of construction of the narrative in an attempt to unite the technique to the theory of media in order to give our contribution to the studies applied to contemporary documentary .